2002
DOI: 10.1023/a:1019858428449
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: With such data, a refined, predictive relationship between the in vitro and the in vivo solubilization with additional information concerning the bile salt/lipid concentration in the human intestine appears possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Several studies have demonstrated a correlation between drug lipophilicity and improved compound solubility in biorelevant media relative to the corresponding intrinsic water solubility (15)(16)(17)(18). Addition of FA and MG, which are formed during digestion of triglycerides, can simulate the fed state.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a correlation between drug lipophilicity and improved compound solubility in biorelevant media relative to the corresponding intrinsic water solubility (15)(16)(17)(18). Addition of FA and MG, which are formed during digestion of triglycerides, can simulate the fed state.…”
Section: Introductionmentioning
confidence: 99%
“…The CMC of the mixed micellar system was deemed to be 0.0046 M based on the average value of the CMCs of the bile salts included in the mixture in 0.15 M NaCl [NaTC CMC = 0.004 M (Natalini et al, 2014), NaDC CMC = 0.0024 M (Natalini et al, 2014), NaTDC CMC = 0.0024 M (Natalini et al, 2014), NaC CMC = 0.0075 M (Reis et al, 2004), NaGC CMC = 0.009 M (Natalini et al, 2014) and NaGDC CMC = 0.0022 M (Natalini et al, 2014)]. The bile salt–lecithin mixed micellar solution was used over a concentration range 0.005–0.017 M. The mixed micellar system was prepared in molar ratios similar to that present physiologically (Wiedmann et al, 2002). …”
Section: Resultsmentioning
confidence: 99%
“…The resultant solution was sonicated for 30 min then stored for 12 h before use. Dilution was carried out in this way as the 2 mM mixture is considered to be the monomer bile salt concentration that is required to be kept constant in each solution in order to keep the size of the micelle constant while its concentration is being changed (Wiedmann et al, 2002). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, over 50% of the drugs considered to be potential candidates in the full development pipeline are poorly soluble in aqueous solutions, and more than 30% are rejected because of unfavourable pharmacokinetic properties [37,38]. Numerous methods have been developed to improve solubility and bioavailability of drugs [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%